2017
DOI: 10.1108/hff-03-2016-0085
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady double-diffusive buoyancy-induced flow in a triangular solar collector shape enclosure with corrugated bottom wall

Abstract: Purpose The purpose of this investigation is to determine the nature of the flow field, temperature distribution and heat and mass transfer in a triangular solar collector enclosure with a corrugated bottom wall in the unsteady condition numerically. Design/methodology/approach Non-linear governing partial differential equations (i.e. mass, momentum, energy and concentration equations) are transformed into a system of integral equations by applying the Galerkin weighted residual method. The integration invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The behavior of the fluid flow driven by a combination of temperature and solute concentration gradients is called double-diffusive convection (Gireesha et al , 2017; Rahman et al , 2017; Moderres et al , 2017; Akbar et al , 2016; Chen et al , 2013). In recent period, double-diffusive convection may appear in a wide range of scientific fields such as biology, oceanology, astrophysics, geology, chemical processes, crystal-growth techniques and the situations in which both the concentration gradient and temperature gradients are in the vertical direction (Subhashini et al , 2011; Mahdy, 2010; Nield and Kuznetsov, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the fluid flow driven by a combination of temperature and solute concentration gradients is called double-diffusive convection (Gireesha et al , 2017; Rahman et al , 2017; Moderres et al , 2017; Akbar et al , 2016; Chen et al , 2013). In recent period, double-diffusive convection may appear in a wide range of scientific fields such as biology, oceanology, astrophysics, geology, chemical processes, crystal-growth techniques and the situations in which both the concentration gradient and temperature gradients are in the vertical direction (Subhashini et al , 2011; Mahdy, 2010; Nield and Kuznetsov, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al [18,19] studied numerically the transient heat and mass transfer in a triangular solar collector with a focus on the effect of the buoyancy ratio. It was shown that that heat and mass transfer increase by increasing the buoyancy ratio and Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection occurs because of the motion and mixing of fluid, induced by the density variations based on the temperature difference within the fluid. Natural convection has been extensively studied in recent works because of its wide variety in various applications (Siddiqa et al , 2015; Shirvan et al , 2017a, 2017b; Rahman et al , 2017; Oztop et al , 2017; Biswal and Basak, 2017; Sheremet et al , 2018a; Sheremet and Pop, 2018; Gerdroodbary et al , 2018; Chen et al , 2018; Pichandi and Anbalagan, 2018; Revnic et al , 2018; Wang et al , 2018; Ismail et al , 2019; Wong et al , 2019). The fluid flow in natural convection is strongly dependent on the shapes of containers.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection in the triangular container was studied extensively for various industrial applications (Joudi et al , 2004; Oztop et al , 2007; Kent et al , 2007; Oztop et al , 2012; Sun and Pop, 2014; Saha and Gu, 2015; Sojoudi et al , 2015; Rahman et al , 2017; Oztop et al , 2017; Das et al , 2018). A few works are explained next.…”
Section: Introductionmentioning
confidence: 99%